Food Dessert No More, They’re Getting a Grocery Store: Plains Grocery Store Initiative - Ewoldt, Laina E. (My University, 2019)
Plains, a small town in western Kansas, has started working towards building a grocery store after years of being a food desert. They reached out to the K-state extension office for assistance in adding a nutrition component to the store. The project began with a broad focus of providing nutritional information for individuals with altered needs, and over the years it was focused into creating information for an in-store kiosk. The kiosk will contain articles, product considerations, and healthy recipes. The kiosk will also ideally have an online component so customers can easily access the information when away from the kiosk. The information contained on the kiosk will hopefully provide customers guidance on how to make healthy dietary choices applicable to them and their needs.